Weed Control in Pepper - William M. Stall (EDIS, 2007)
Revised! HS-199, a 5-page fact sheet by William M. Stall, provides recommendations for total farm weed management in pepper production. Includes a table listing chemical weed controls for peppers in Florida. Published by the UF Department of Horticultural Sciences, November 2007.